Utilization of Android-Based ToSM (Test of Second Mathematics) Instrument for Mapping Intuitive Basic Calculation Competencies (IBCC) in Students - Ade Machnun Saputra; Rini Sugiarti (Ittishal Educational Research Journal, 2021)
This research aims to find out the usefulness of an android-based ToSM (test of second mathematics) instrument for mapping the competency of intuitive basic calculation (CIBC) in students. ToSM (Test of Second Mathematics) is the standard instrument of Mathematics Seconds to measure IBCC (Intuitive Basic Calculation Competencies). ToSM only covers arithmetic operations (addition, subtraction, multiplication, and division), most essential. ToSM measures the number of operation counts per minute (OPM), time per operation category completion. The method used in writing review literature begins with the selection of topics. It then determines the keywords for the search for journals so that several journals are selected to be analyzed. Searches for the journal through google scholar are limited from 2015 to 2021. Meanwhile, the keyword used is "ToSM Seconds Mathematics." This research was conducted by reviewing journals or literature related to this study plus statistical data and scientific works related to ToSM, which the Center for The Development of Mathematics Seconds (CDMS) team updates. Mapping essential calculation competencies among students are no less critical because ToSM has other uses, namely as an instrument to train concentration and resilience in learning.